Measure of creativity and innovation: evidence of validity in the Brazilian context - Gondim, Sônia Maria Guedes; Techio, Elza Maria; Loiola, Elisabeth; Carias, Iago Andrade; Colman, Katlyane; da Costa, Silvia; Paez, Dario; Sánchez, Flor (Revista de Administração da UFSM, 2020)
The main objective of this article is to explore the validity of the Factors of Creativity and Organizational Innovation (FINO) Measure in a Brazilian sample and ascertain the predictive power of individual, group, and organizational factors in relation to the perceived innovation in the organization. Evidence of the validity of this measure was previously found with workers in the Basque Country and in Latin-American countries. A total of 265 workers from various organizations participated in this survey study. Confirmatory factor analysis (CFA) and linear regression analysis with observable variables were performed by means of structural equation modeling. The CFA results indicate that the model with the best fit has eight correlated factors. The regression analysis suggests that the factors Work Characteristics, Leadership, and Personal Traits for Creativity and Innovation predict the perception of innovation in the organization.